1993
DOI: 10.1182/blood.v82.1.118.bloodjournal821118
|View full text |Cite
|
Sign up to set email alerts
|

Human megakaryocytes express clusterin and package it without apolipoprotein A-1 into alpha-granules

Abstract: Clusterin, a 70-Kd disulfide-linked two-chain plasma glycoprotein circulates in blood as a high-density lipoprotein particle and is highly induced after tissue injury and tissue remodeling. In this study, peripheral blood leukocytes were assayed for clusterin expression. The protein was predominantly detectable in human platelets by immune cytochemistry. The content of clusterin was determined and amounts to 2.5 +/- 1.3 micrograms/10(9) platelets, thus representing about 2% of the blood pool. Clusterin purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 28 publications
2
17
0
1
Order By: Relevance
“…Enrichment of Apos in PLC‐EVs correlates with earlier data 65,66 . ApoA‐I is central for high‐density lipoprotein (HDL)‐mediated lipid efflux and as precursor protein was shown to be expressed in PLTs 67 .…”
Section: Discussionsupporting
confidence: 71%
“…Enrichment of Apos in PLC‐EVs correlates with earlier data 65,66 . ApoA‐I is central for high‐density lipoprotein (HDL)‐mediated lipid efflux and as precursor protein was shown to be expressed in PLTs 67 .…”
Section: Discussionsupporting
confidence: 71%
“…CLU is a glycoprotein that has a functional role in pro-survival and cell cycle control [ 53 ]. Ordinarily, it is the platelets and megakaryocytes that expressed the CLU which is localized in the alpha granules [ 54 ]. It is reported that CLU protein expression decreased in systemic lupus erythematosus patients’ platelets and interacted with thrombotic complications [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although clusterin interferes in several system, little is known about the biological impact of the protein (33). Many tissues express clusterin mRNA, including testis, prostate, kidney, brain, adrenal medulla, liver, pituitary gland, ovary, synovia, thymus and bone marrow (megakaryocytes) (34)(35)(36)(37)(38). HepG2 cells (22), but also other cell lines (28) have been shown to secrete clusterin, and the main source of serum clusterin has not been identified.…”
mentioning
confidence: 99%